1982
DOI: 10.1007/bf03007747
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic considerations in down’s syndrome: experience with 100 patients and a review of the literature

Abstract: Down's Syndrome (Trisomy 21, T21) occurs in approximately 0.15 per cent of live births. In addition to the stigmata of the syndrome, other congenital defects are frequently found in these patients. Cardiac lesions are particularly prominent.To determine the complications associated with anaesthesia and surgery we examined the records of 100 consecutive patients (58 males, 42 females) who underwent surgery with general anaesthesia during a two year period, from March 1978-March 1980 In addition to the cardiac l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
4
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 27 publications
0
35
4
1
Order By: Relevance
“…Other medical problems that could affect the anesthetic results include pulmonary hypertension, polycythemia in the neonatal population, and thyroid function abnormalities. Although Kobel et al [1982] reported no differences in regard to the response of 100 patients with DS who inhaled anesthetic agents, Borland et al [2004] reviewed 930 anesthetic procedures in children with DS and found that the most common anesthetic-related complications included bradycardia, which was severe in 3.66%, airway obstruction in 1.83%, difficult intubation in 0.54%, and post-intubation croup in 1.83%. Although the total number of children reviewed was small, Mitchell et al [2003] found a 27% incidence of postoperative complications in 13 children who required PE tube placement.…”
Section: Anesthetic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other medical problems that could affect the anesthetic results include pulmonary hypertension, polycythemia in the neonatal population, and thyroid function abnormalities. Although Kobel et al [1982] reported no differences in regard to the response of 100 patients with DS who inhaled anesthetic agents, Borland et al [2004] reviewed 930 anesthetic procedures in children with DS and found that the most common anesthetic-related complications included bradycardia, which was severe in 3.66%, airway obstruction in 1.83%, difficult intubation in 0.54%, and post-intubation croup in 1.83%. Although the total number of children reviewed was small, Mitchell et al [2003] found a 27% incidence of postoperative complications in 13 children who required PE tube placement.…”
Section: Anesthetic Considerationsmentioning
confidence: 99%
“…An association between DS, stridor, and/or subglottic stenosis is frequently discussed in the anesthesia literature [Kobel et al, 1982;Sherry, 1983;Miller et al, 1986;Borland et al, 2004]. It has been common practice over the years to use a smaller endotracheal tube when intubating children with DS.…”
Section: Anesthetic Considerationsmentioning
confidence: 99%
“…Cardiac defects are present in 40 to 50% of patients with DS. 117 Combinations of the foregoing abnormalities predispose patients undergoing spine surgery to upper-airway obstruction, making their airway management difficult. Normal films of the cervical spine in patients with DS are reassuring, particularly during intubation and positioning for scoliosis-related procedures.…”
Section: Down Syndromementioning
confidence: 99%
“…In addition to the stigmata of the syndrome, other congenital defects are frequently found in these patients. Cardiac lesions are particularly prominent 3 . Congenital heart disease such as endocardial cushion defects, VSD, ASD, isolated secondum atrial defect, PDA, Tetralogy of Fallot.Children with Down syndrome are more prone to sleep apnea and airway obstruction due to a large tongue, short neck and laryngomalacia 4 .There is also increased incidence of atlanto axial instability and risk of spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%